Evaluating the effectiveness and calculating the rate of return on investment of training courses using Kirk Patrick and Phillips models - Hossein Ashofteh; Elaheh Orangian (Institute of Management fekrenoandish, 2021)
Extended Abstract Abstract The aim of this study is to evaluate the effectiveness and calculate the rate of return on investment of training courses in factories and production workshops. To achieve this, Kirk Patrick's model was used to design the questionnaires and measure effectiveness, and the Phillips model was used to calculate the return on investment. The research method is descriptive-analytical case study, the statistical population of production factories and the statistical sample is one of the production factories in which the data related to the training course have been examined. The validity and reliability of the data obtained from the questionnaires were monitored by experts' opinions and Cronbach's alpha test, respectively, and the data were analyzed using one-sample t-test, two-sample t-test and skew-elongation normality test (inferential statistics). Descriptive features of the data (descriptive statistics) are also given. The software used in this research is Microsoft Excel,&SPSS, and Shannon entropy method has been used to differentiate the effects of training from other criteria affective on changes in benefits after training courses. Also, in addition to calculating the return on investment, the cost-benefit ratio and net present value have been calculated to reinforce the results and take into account the time value of money. The results of the study indicate a high rate of return on investment higher than 100%, a cost-to-benefit ratio higher than one and, a positive net present value, and finally the financial and economic justification for holding the training course. Introduction Nowadays, most management experts believe that it is no longer the production line, technology and massive financial resources of an organization that brings a competitive advantage, but the management of the organization's human resources that creates value (Ziaei et al., 2011). In addition, it is important to note that macroeconomics is closely related to microeconomics (Orangian et al., 2021). Therefore, developing human resources in the organization is vital and training employees and turning them into human capital and key players is very strategic and important. Although human capital has been discussed since the time of classical economists, what has been considered in recent decades is the modeling and presentation of models in which human capital is considered. In other words, while the classical viewpoint belived that production was assumed to be only a function of labor and capital, the qualitative factor of labor or human capital must also be included as a variable in these functions. On the other hand, rapid developments in science and technology require adaptation to these changes. Thus, cultural, social, technological, economic and political pressures have forced organizations to pay special attention to their potential, especially staff training and improvement. Training of employees assumes to be all training programs and activities designed within the framework of the employee training system in order to increase and improve the level of competence and capability of formal, contractual and specific work employees (both employees and managers) to improve productivity and efficiency of executive bodies. It is said to be implemented (Sabzipor et al., 2017). Accordingly, in order to improve the efficiency and effectiveness of the executive departments, the organization is obliged to design the staff training system in such a way that along with matching the knowledge, skills and attitudes of employees with the desired job, provide the necessary incentives for continuous participation of employees in the training process in such a way that a relationship is established between staff promotion and managers and training, and enjoy a minimum per capita training hours according to the relevant regulations each year (Mohamadi et al., 2015). However, it is important to note that what is meant by education is effective, efficient, and productive education in general. In this case, staff training can pave the way for employee improvement, turning them into human capital and organizational excellence. According to the above, evaluating the effectiveness and calculating the rate of return on investment is necessary to hold any training course in the organization. Finally, the main purpose of this study is to achieve the effectiveness and ROI of holding a training course in one of the lines of a manufacturing plant. The course was held with the participation all of the twenty line employees and the economic feasibility of the course was examined through Kirk Patrick and Phillips models. Theoretical framework There are several models for evaluating training courses, the most important of which is the Kirk Patrick model. In this model, four levels are proposed for training evaluation. The first level is called the reaction level, which is the level of reaction that learners show to all the factors affecting on the implementation of a training course. The second level is the level of learning, determining the level of skills, techniques and learning facts that are taught to learners in the training course and can be understood through previous training, during and after the course. The third level is the level of behavior, which means the behavior, manner and amount of changes in the behavior of participants that occur as a result of participating in the training course and can be clarified by continuing to evaluate the actual work environment. Finally, the fourth level is the outcome level, which refers to the extent to which goals are directly related to the organization (Kirk Patrick, 1996). Another suitable model for evaluating organizational training courses is the Phillips investment return model. The ROI or Phillips model is the result of the development of the Kirk Patrick model. Investment Return is the fifth level added to Patrick's four-level model (reaction, learning, behavior, and outcomes). In this model, Phillips shows how monetary or financial sums should be included in the value of education and the return on investment in an educational activity calculated. Cost-benefit rate and net present value are also calculated. Cost-benefit rate is the result of dividing benefits by costs, and if this ratio goes above one, the plan is economically justified. Net present value is also a dynamic method of financial evaluation of projects that takes into account the time value of money. It is very clear that the value of one thousand Tomans at the moment is different from one thousand Tomans a year later; because you can get future benefits from one thousand Tomans now until next year. This is true even in the absence of inflation. As a result, the value of the future currency can be converted to the present value with an arbitrary discount rate (in the recent study, 10% due to the minimum bank interest). (Taghinezhad.et al.2020) In a study entitled "Designing a Model" for return on investment in the education system of executive employees, they concluded that the level of education's effect on future income of individuals is greater than that of other variables. There was a positive and significant relationship between the rate of return of training courses and income of individuals. The results also indicate that the rate of return on investment in the educational system of executive employees has a direct and significant relationship with the variables of gender, type of residence and type of marriage (rezaie Siroos. Er al. 2020). In a study entitled presenting the predictive model of the return on investment in training and improvement of the human source based on the organizational culture components and professional competency the concluded that training and improvement of human source and evaluation of the process of expense to benefit and the rate of the return on investment is effective on the training programs (Nouri, et al.2019). In a study entitled Calculating the rate of return on capital of specialized courses of Pars Oil and Gas Company, they concluded that evaluation indicators as well as the way of calculating and identifying the net share of education are among the important and necessary points, and its effective implementation will contribute to the transfer of learning and ultimately lead to an increase in the rate of return on investment.